Industrial training report: Malaysian Communication and Multimedia Commission (MCMC) / Aliff Danial Amran Suhaimi - Amran Suhaimi, Aliff Danial (Perpustakaan Tengku Anis (PTA), 2017)
Malaysian Communication and Multimedia Commission (MCMC) or Known as Suruhanjaya Komunikasi dan Multimedia Malaysia (SKMM) is one of the commission that give a lot of experience to the trainee which is experience in the organizational itself and outside the organisation in the way to give and expose trainee best experience during internship. The experience involving of Management of User training, Record Keeping, Engaging with crowd that shown in this special project was helping trainee in the industry for future even will give a lot of knowledge as well as new experience.